Student Motivation in Online Learning for Advanced Civics Courses - Dita Afianti; Banu Setyo Adi; Inggit Dyaning Wijayanti (STAI Hubbulwathan Duri, 2022)
Implementing a distance learning system has resulted in all teaching and learning activities innovated with online learning that can be accessed via distance. In this case, students certainly experience different difficulties and challenges. The encouragement and motivation from students to keep the spirit of following the lesson will determine the success of learning. This study aims to determine students' motivation to learn in online learning for advanced Civics courses at the PGMI study program at UIN Sunan Kalijaga Yogyakarta. This type of research is descriptive qualitative research, and the subject is students in the Advanced Civics course, totalling 33 students. Data collection techniques in this study were interviews and questionnaires. The data analysis technique uses an interactive model of Miles's theory; Huberman and Saldana analyze data in three stages: data condensation, presenting data (data display), and drawing conclusions or verification (conclusion drawing and verification). The results showed that the Advanced Civics Study Program students at the PGMI UIN Sunan Kalijaga Yogyakarta had high motivation, obtaining 72.66%. This means that even though students have undergone online lectures with a distance learning system for 4 semesters, it does not affect students' motivation to continue learning, even though there are several obstacles during the process. The results showed that the Advanced Civics Study Program students at the PGMI UIN Sunan Kalijaga Yogyakarta had high motivation, obtaining 72.66%. This means that even though students have undergone online lectures with a distance learning system for 4 semesters, it does not affect students' motivation to continue learning, even though there are several obstacles during the process. The results showed that the Advanced Civics Study Program students at the PGMI UIN Sunan Kalijaga Yogyakarta had high motivation, obtaining 72.66%. This means that even though students have undergone online lectures with a distance learning system for 4 semesters, it does not affect students' motivation to continue learning, even though there are several obstacles during the process.